Karl Polanyi. Remettre l'économie à sa place - Behrent, Michael C. (Sciences humaines, 2016)
History

Le rendement et le butin. Regard écologique sur l'histoire du capitalisme, The Yield and the Booty. An Ecological Perspective on the History of Capitalism - Charbonnier, Pierre (Actuel Marx, 2013)
This article examines the history of globalized capitalism from the perspective of the relations to the environment which it helped to construct. It proposes a definition of globalized capitalism as a form of relation to nature. If philosophy has frequently postulated that modernity is characterized by the dissociation between the natural and the social, the history of the economic take-off of the states of Western Europe throws a singular light on this hypothesis. Combining a reading of Karl Polanyi and Kenneth Pomeranz, it can be argued that the logic of commodity always tends to render invisible the relations to the environment which define capitalism. The temporal and spatial lag between those populations which live the concrete experience of the industrial revolution and the enormous natural resources required for its appearance enable us to understand how it has been possible for the representation of the economy to become so radically dissociated from its natural metabolism.
History; Political Science
Keywords: globalized capitalism; nature and society; political thought

Cité et réciprocité, City and Reciprocity : The Role of Cultural Beliefs in the Roman Economy - Verboven, Koenraad (Annales. Histoire, Sciences Sociales, 2012)
La nouvelle économie institutionnelle est devenue populaire dans la recherche de l’économie antique depuis une dizaine d’années. Pourtant la notion de « croyances culturelles », qui joue un rôle central dans l’œuvre de Douglass North et dans les analyses du changement institutionnel par Avner Greif, a été largement ignorée. J’affirme qu’une approche néo-institutionnelle qui utilise cette notion de « croyances culturelles » offre une meilleure voie pour comprendre l’influence des idéologies et des valeurs morales sur l’économie antique que le modèle de Moses Finley. Des croyances culturelles ne sont pas des contraintes déterministes sur le comportement humain, mais elles aident à orienter les prises de décision et permettent d’anticiper les (ré) actions des autres. J’étudie deux ensembles de normes et de valeurs qui, dans la culture romaine, ont profondément marqué le cadre institutionnel de l’économie. L’un était centré sur la réciprocité. Ses normes et valeurs ont permis de construire et de maintenir des réseaux sociaux au-delà du groupe de la familia étendue avec ses affranchis. Elles étaient à la base du développement de la loi des obligations et de la représentation. L’autre se fondait sur la cité. Il a formé la culture politique en créant des droits et des obligations personnelles et en imposant des demandes légitimes aux élites politiques de défendre ceux-ci et de garantir et de stimuler des intérêts privés et communs. Le droit romain et la justice étaient ses résultats les plus importants. Idéologiquement, l’Empire romain se présentait comme une méta-cité qui incorporait les communautés locales qui, à leur tour, étaient graduellement transformées sur le modèle de la cité. Ces deux ensembles de croyances culturelles ont baissé les coûts de transactions, mais ils n’ont jamais menacé la prééminence de l’aristocratie locale et impériale. Vers la fin du IIe siècle de notre ère, les cités locales se sont affaiblies tandis que l’administration impériale se renforçait. Les aristocraties locales et régionales se sont tournées vers la bureaucratie et l’armée impériales pour maintenir leur rang social, leur influence et leur pouvoir. L’idéologie de la cité comme principe dominant de la culture politique devenait soumise à celle de l’empereur sacral, garant de la justice et de l’ordre divins. EN: New Institutional Economics have become popular in ancient economic history research the past decade. However, the notion of “cultural beliefs” that plays a central role in Douglass North’s recent work and in Avner Greif’s analysis of institutional change, has been largely ignored. I argue that a neo-institutional “cultural beliefs approach” offers a better way to understand the influence of ideology and moral values on the ancient economy than the Finley model does. Cultural beliefs are no deterministic constraints on human behavior but help to orient decision making and allow anticipating the (re)actions of others. I explore two key sets of norms and values in Roman culture that profoundly marked the economy’s institutional framework. One centered on reciprocity. Its norms and values supported social networks beyond the confines of the familia-freedmen group and underlay the development of contract and agency law. Another set rested on citizenship. It shaped political culture by creating individual rights and obligations and laying legitimate claims on political elites to enforce these and to take action to secure and stimulate private and common interests. Roman law and the distribution of justice was its prime off-spring. Ideologically the Roman Empire presented itself as a meta-city that incorporated local communities which in turn were gradually transformed to fit the civitas model. Both belief sets lowered transaction costs, but they never threatened the preeminent position of local and imperial aristocracies. Towards the end of the second century CE local communities became weaker while the imperial administration grew stronger. This caused local and regional aristocracies to turn to the imperial court and army for status, influence and power. The ideology of citizenship as the guiding principle of political culture gave way to that of the sacred emperor who guaranteed divine justice and order.
History
Keywords: Roman Empire; ancient economic history; ancient economies; cultural beliefs approach; institutional economics

La société contre le marché - Skornicki, Arnault (The Life of Ideas, 2012)
A propos de : Karl Polanyi, La Subsistance de l'homme. La place de l'économie dans l'histoire et dans la société, Flammarion
History; Sociology
Keywords: capitalisme; commerce; marché

À propos de « ceux qui sont en dehors de la société ». L'indigent et l'assistance publique au Québec dans la première moitié du XXe siècle - Petitclerc, Martin (Revue d'histoire de L'Amerique francaise. automne2011/hiver2012, Vol. 65 Issue 2/3, p227-256. 30p., 2011)
The “ Loi établissant le service de l'assistance publique" (Public Welfare Act) sparked considerable controversy after its adoption in 1921 .The Act provided for provincial and municipal grants to private and religious institutions providing shelter to the poor and destitute. Led by Henri Bourassa, among others, the debate concerned the problem of state intervention in an area traditionally conceived of as the responsibility of the Church. In contradiction to Bourassa's theories, most historians analyzed the A c t through the rubric o f modernization as a necessary affirmation of State prerogatives in the area of social protection. In this article, we argue that this Act is an attempt (largely successful) to consolidate a form of liberal governmentality based on, since the 19th century, what Karl Polanyi termed “the figure of the pauper" According to this perspective, the 1921 A c t is not a significant stage in the age-old struggle between Church and State, but rather a time of reform in liberal politics in regards to "the indigent 'The latter leggally defined as unable to work and without family support, and therefore “ outside of society," an expression of the day, allowed justifying the development o f a private/public system of charitable assistance against the project o f social policies founded on a universal conception of social rights. The article presents this dynamic through an analysis of the contentious issue of the rights of indigents to public assistance. (English)
History
Keywords: BOURASSA; Henri; 1868-1952; Canada; Quebec; church & state - Canada; liberalism - Canada; poor people - Canada; poor people - government policy; poor people - services for - history; public welfare - Canada - history

Karl Polanyi : une voix du siècle passé, Abstract - Cangiani, Michele (Revue du MAUSS, 2009)
RésuméSituer Karl Polanyi dans son temps et par rapport aux grandes théories sociales du passé, y compris celle de Marx, nous permet de mieux comprendre les problèmes du temps présent. C’est de ce point de vue que l’article cherche à mettre brièvement en relief quelques aspects de la contribution de Polanyi à la connaissance historique, à la critique de la science économique et à la théorie politique., To consider Karl Polanyi’s thought in relation to his time and to great social theories of the past, Marx’s theory to begin with, can improve our understanding of problems of current times. This is the starting point of this article’s attempt to synthetically focus some aspects of Polanyi’s contribution to historical knowledge and political theory, and of his critique of economics.
History
Keywords: political theory

Essais, Karl Polanyi, Sciences humaines - Seuil - Cangiani et al. (2008)
Essais, Karl Polanyi : L’ouvrage qui vaut à Polanyi une renommée mondiale ( La Grande Transformation paru en 1944) ne fut traduit en français qu’en 1983, signe (et cause aussi) d’une trop longue négligence pour un auteur désormais reconnu pour son apport incontestable aux sciences humaines et sociales ENG translation: The book which earned worldwide fame Polanyi (The Great Transformation, published in 1944) was not translated into French in 1983, a sign (and also because) of too long neglect for an author now recognized for his contribution Incontestable to the human and social sciences. Just back from the pendulum, this relative forgetfulness has given way to growing attention. This renewed interest is all the more justified because the thought of Polanyi is astonishingly topical. He is indeed the thinker par excellence of the "market society" and of the crisis to which a society is exposed where the logic of the market economy comes to dominate all spheres of human activity. Actually, Polanyi is still by his conception of a radically democratic socialism supposed to fulfill the modern ideal of freedom, by the weight it gives to culture and institutions in the analysis of economic systems, by its multidisciplinary method And by so many other traits which make it a reference today unavoidable in all the social sciences. These texts (mostly unpublished in French) offer a panorama of Polanyi's thought. There are of course keys to accessing the heart of the analysis grid proposed in The Great Transformation, but also a tool bringing together most of Polanyi's contributions to economic anthropology, the comparative study of systems Economics, political philosophy, and the analysis of systems and ideologies that clashed in the twentieth century (socialism, communism, fascism, Nazism).
History

Karl Polanyi, le marché et le socialisme - Skornicki (2008)
La société est-elle condamnée à subir les lois du marché ? La publication d'Essais inédits de l'économiste Karl Polanyi permet de redécouvrir le (...)
History; Sociology
Keywords: capitalisme; fascisme; marché; socialisme

Autour de Polanyi : vocabulaires, théories et modalités des échanges - Clancier, P.; Bresson, Alain (Editions De Boccard, 2005)
The varied questions which arise from the contributions made in this work provide a new modernity to Karl Polanyi and show the major interest in bringing together, as openly as his own, the various historical and economic specialties , Archaeological, ethnological, present in the House of Archeology and Ethnology of Nanterre. One of the most stimulating aspects of the contributions gathered here is the importance given to the presence of men, far beyond the simple equation of economic relations. These contributions sweep away a voluntarily vast field, from antiquity to the contemporary world. The historiographical dimension of Karl Polanyi's career is also present, through the contributions of Anne Chapman, who worked with him in South America, and his daughter, Kari Polanyi Levitt, specialist in development economics. Nathalie Zemon Davis, historian of societies in modern Europe, was asked to present the general conclusions of this symposium. Collection Conferences of Archaeology & Ethnology Maison René-Ginouvès , n o 1
History
Keywords: CHAPMAN; Anne; POLANYI LEVITT; Kari; ZEMON DAVIS; Nathalie

Karl Polanyi et la séparation institutionnelle entre politique et économie - Buğra, Ayşe (Raisons politiques, 2005)
This article explores Karl Polanyi’s analysis of the institutional separation of politic and the economy in the context of the 19th century market economy. The contribution his analysis could make to the quest for viable alternatives to the contemporary neo-liberal international order depends on how we construe two key concepts in his work, “disembeddedness” and “countermovement”. In this regard the author suggests that: 1) In Polanyi’s work the disembedded economy appears not as a sociological reality but as a political project, and 2) Polanyi’s analysis of the countermovement does not justify all types of resistance to the market economy as humane and politically acceptable.
Economics; History
Keywords: institutional separation

Le port de commerce : un concept en débat - Graslin, Laetitia; Maucourant, Jérôme (Topoi, 2005)
Economics; History
Keywords: Dahomey and the Slave Trade; port of commerce